Are Secondary School Students Motivated to Learn Islamic Education? - Muhammed-Lawal, Adam Adesina; Abd Rashid, Adnan; Badrasawi, Kamal J I (Society for Science and Education, United Kingdom, 2018)
The main aim for Islamic Education is to produce a ‘good man’ in all his personality aspects. This study aims to determine the level of secondary school students’ motivation in learning Islamic Education subject, and to examine the factors influencing their motivation using the cross-sectional survey design. The study sample consisted of (170) students selected from an Islamic school in Malaysia using a nonrandom, quota sampling procedure to answer a 32-item questionnaire. The items measured four constructs: Students’ Motivation (SM), Parental Influence (PI), Teaching Pedagogy (TP) and Teachers’ Morality (TM) using a 5-point Likert scale. Descriptive statistics (Frequencies, Percentages, Means and Standard Deviations) and Pearson product-moment correlation coefficients were used to analyze the collected data. The results show that students’ motivation in learning Islamic Education subject is quite high. The Islamic Education subject is important for students as it helps them appreciate and improve their life. Moreover, there were significantly positive relationships between the three factors (i.e. Parental Influence (PI), Teachers’ Morality (TM), Teaching Pedagogy (TP) ) and Students’ Motivation (SM). It is recommended that teachers of Islamic Education should use more interactive teaching methods to further motivate students to learn Islamic Education and be able to apply the contents in their life. There is a need for more quantitative research to be conducted on larger samples and using other statistical techniques. Qualitative research is also needed to get more in-depth information on students’ motivation in learning Islamic Education.